Caracterización del Uso de las Tecnologias de Información y Comunicación (Tic) en las Pequeñas Empresas del Municipio de Villavicencio (Meta) por Derly Rodriguez Murillo (2013)
The new economy has transformed the manufacturing and industry by the advent of information technology and communication ICT, which generate production development, productivity, competitiveness and the degree of readiness to promote growth in open systems Villavicencio small businesses, as this generates constant exchange with other surrounding systems through complex interactions. Accordingly we developed a research to know the use of ICT's in Villavicencio, where it was observed that 100% of the organizations surveyed have at least two tools of information and communication for service in relation to the groups of interest, but do not give them the proper use by problems of resistance to change.